Ranitidine Loaded Biopolymer Floats: Designing, Characterization, and Evaluation. (14th December 2017) - Karim, Abdul; Ashraf Shaheen, Muhammad; Mehmood, Tahir; Raza, Abdul Rauf; Aziz, Musadiq; Din, Badar
Abstract : The float formulation is a strategy to improve the bioavailability of drugs by gastroretentive drug delivery system (GRDDS). A drug delivery model based on swellable and reswellable low density biopolymers has been designed to evaluate its drug release profile using ranitidine (RNT) as a model drug and formulations have been prepared utilizing 3 2 factorial designs. The drug release (DR) data has been subjected to various kinetic models to investigate the DR mechanism. A reduction in rate has been observed by expanding the amounts of PSG and LSG parts, while an expansion has been noted by increasing the concentration of tragacanth (TG) and citric acid (CA) with an increment in floating time. The stearic acid (SA) has been used to decrease the lag time because a decrease in density of system was observed. The kinetic analysis showed that the optimized formulation (S4F3) followed zero-order kinetics and power law was found to be best fitted due to its minimum lag time and maximum floating ability. The resemblance of observed and predicted values indicated the validity of derived equations for evaluating the effect of independent variables while kinetic study demonstrated that the applied models are feasible for evaluating and developing float for RNT.